(untitled) (Orinoquia, 2004)
Titulo en ingles: Diagnostic and treatment of the granulosa cell tumor of colombian mare creole. RESUMEN: Los tumores ováricos son de re- lativa importancia en la prácti- ca reproductiva equina, dentro de estos, el tumor de las células de la granulosa (TCG) es el de mayor presentación, aunque no se conoce con profundidad la patogénesis. Se sugiere que la falla en la ovulación mas otros factores adicionales pueden tener importancia. Este artículo describe los signos clínicos, ultrasonografía, niveles hormonales, histopatología, diagnóstico y tratamiento de un TCG en una yegua criolla colombiana llevada para consulta a la clínica de grandes animales de la Universidad de los Llanos. La descripción de este caso podría servir de ayuda a los clínicos particulares en la orientación objetiva del diagnóstico, ante nuevos reportes, dado el significativo crecimiento de esta industria. Palabras clave: equino, neopla- sia, células de la granulosa, reproducción ABSTRACT: The ovarian tumors are of relative importance in the practices it reproductive equine, inside these, the granulosa cell tumors (TCG) it is that of more presentation, although one doesn’t know with depth the pathogenesis. It is suggested that the fails in the ovulation but other additional factors can have importance. In this article case of equine granulosa cell tumors is reported, diagnosed by the clinical signs, ultrasonographic examination, hormonal levels, histopathology, diagnosis and treatment of a TCG in a Colombian Creole Mare taken for consultation to the clinic of big animals of the Llanos University. The description of this case could serve from help to the practitioner clinical in the objective orientation of the diagnosis, before new reports, given the significant growth of this industry. Key words: Equine, Mare, Granulosa Cell tumors, Repro- duction.